Analysis of Work–Life Balance and Workload on Turnover Intention Through Job Satisfaction as A Mediating Variable Among Generation Z in Surakarta - Nuzul Alfirizqy Azzahra; M Farid Wajdi (Jurnal Economic Resource, 2026)
This study examines the effects of workload and work-life balance on Generation Z's decision to leave Surakarta, with job satisfaction as a mediating factor. The approach adopted in this research is a causal association design using a quantitative method. The information used in the study came from a survey conducted among Generation Z employees in the region surrounding Surakarta, using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) with SmartPLS. The study's conclusions demonstrated that workload positively affects turnover intention, that work-life balance positively affects job satisfaction, that workload negatively affects job satisfaction, and that work-life balance has no direct impact on turnover intention. Additionally, it was established that turnover intention is negatively impacted by work satisfaction. Regarding the test of the mediating variable, it was confirmed that job satisfaction mediates the impact of work-life balance on turnover intention, but not the impact of workload. The research's conclusions indicate that work-life balance and workload are very important, as appropriate work-life balance can improve job satisfaction and decrease turnover intention amongst Generation Z workers.